18‐5: A 1058‐ppi 4K Ultrahigh‐Resolution and High Aperture LCD with Transparent Pixels using OS/OC Technology. Issue 1 (May 2017) - Kawashima, Susumu; Shishido, Hideaki; Oshita, Satoru; Yoshitomi, Shuhei; Yamashita, Akio; Ishitani, Tetsuji; Sato, Ami; Jincho, Masami; Shima, Yukinori; Katayama, Masahiro; Yamazaki, Shunpei
Abstract : A 4.3‐inch 1058‐ppi 4K liquid crystal display was fabricated using top‐gate field‐effect transistors (FETs) comprising a cloud‐aligned composite oxide semiconductor. For transparent pixels comprising an oxide semiconductor/oxide conductor (OS/OC), FETs, wirings, capacitors, and contacts in the pixels are transparent. This display achieves a 63.6% aperture ratio and low power consumption.